COMPARISON BETWEEN CONVENTIONAL HIGH LIGATION AND STRIPPING AND RADIOFREQUENCY ABLATION FOR GREAT SAPHENOUS VARICOSE VEINS - MUSHTAQ , A; SADIQ , I; NASIR , M; SALEEM , MU; SADIQ , MA; SADIQ , MH (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted from December 2022 to May 2023 to assess patient-based, radiological, and clinical outcomes after conventional surgery and radiofrequency ablation for great saphenous varicose veins. Patients were randomly divided to undergo conventional surgery or RFA. American Society of Anesthesiologists fitness grade, Venous Disability Score (VDS), Total Clinical Severity Score (TCSS), Michael’s, and CEAP clinical classes were recorded. VEINES-QoL/Sym questionnaire and Aberdeen Varicose Vein Questionnaire were used to estimate baseline QoL. Patients were called for follow-up at the end of 1st and 5th week. The study was conducted on a total of 110 patients. Patients were randomly divided; 57 underwent RFA, and 53 underwent conventional surgery. Results showed that the difference between both groups regarding anesthesia induction, recovery, and discharge from surgery was insignificant. RFA had significantly longer total theater time compared to conventional surgery. Duplex imaging showed that RFA resulted in successful ablation except in two cases where veins had segmental brisk flow. These cases were retreated successfully. Conventional surgery only had the problem of incomplete stripping (6 cases). Post-operative pain, bruising, and the need for analgesia were significantly higher following conservative surgery. Patients in the RFA group returned to work and normal activities more quickly than the conventional surgery group. It is concluded that RFA had a longer intervention time but significantly better outcomes than conventional surgery.